Determination of stress-strain state of a rock mass on the basis of soundmetric control methods - Romanenko, Andriy; Sydorenko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article defines the main approach to the selection of seismic sensors to obtain the necessary signal that will determine the stress-strain state of the mountain massif. A schematic diagram of equipment for recording and collecting audiometric information has been developed. An approach to signal processing has been developed and primary research on the identification of phenomena has been performed. A number of phenomena that are characteristic of any career are identified and their soundmetric data are determined. Scientific novelty:For the first time, a method was proposed to take into account the degree of disturbance of the board by underground mining through soundmetric observations with subsequent separation of phenomena and selection of the intensity of destruction of the rock mass. Initial conclusions were made regarding the possibility of identifying phenomena and determining the direction where this phenomenon occurred.